Assessing the Impact of Global Financial Crises on International Law and Policy - Dihaa, Dihaa Hadaf; Ahmed, Sundus Serhan; Salih, Rami; Jasim, Bushra Abd Al-Lattif (Journal of Ecohumanism, 2024)
Background: The inexorable tidal wave of global financial crises has long presented multifarious challenges to international law and policy, necessitating critical assessments of the durability and adaptation of global legal and economic frameworks. Objective: This study aims to meticulously assess the impact of global financial crises, focusing on the 2008 crisis and the evolution and adaptation of international law and policy to identify patterns, challenges, and opportunities in the global response to economic calamities. Methods: This study uses a qualitative approach to combine insights from historical analysis, case studies, and a critical assessment of legal and policy texts. The study focuses on occasions when financial crises severely disrupted international legal and policy systems, with analytical frameworks used to assess policy and legal responses and their eventual effectiveness. Results: The study findings show that financial crises generally cause changes in international law and policy, fluctuating between protective isolationism and constructive multilateralism. Various countermeasures have emerged, such as strengthened regulatory frameworks and policy adjustments, indicating efforts to avoid future crises and strengthen global economic stability. Conclusion: There is a clear reciprocal connection between financial crises and international law and policy, demonstrating a dynamic interaction of economic, legal, and political elements. The research emphasizes the need for proactive, resilient, and adaptable legal and regulatory frameworks in navigating the intricacies and multifaceted consequences of financial crises on a worldwide scale. This study lays the groundwork for additional investigation into effective legal and regulatory methods to mitigate the negative consequences of future financial crises.